Positive electrode material wrapped by mixed solid electrolyte, preparation method of positive electrode material, positive electrode plate, solid-state battery and power-related equipment

By wrapping the mixed solid electrolyte on the surface of the positive electrode material of the solid state battery, the problem of poor stability between the interface between the positive electrode material and the solid electrolyte is solved, and the battery capacity is maintained and the charging and discharge efficiency is improved.

CN119786564AActive Publication Date: 2025-04-08SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD

Patent Information

Application Number
CN202411973255.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

During the charging and discharging process of existing solid-state batteries, the stability of the interface between the positive electrode material and the solid electrolyte is poor, resulting in attenuation of the battery capacity.

Method used

The positive electrode material wrapped with mixed solid electrolytes, including oxide solid electrolyte, sulfide solid electrolyte and halide solid electrolyte, is wrapped on the surface of the positive electrode material by ball milling to improve interface stability and conductivity.

Benefits of technology

It effectively improves the structural stability and conductivity of the positive electrode material, extends the cycle life of the battery, reduces capacity attenuation, and improves the charge and discharge efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786564A_ABST
    Figure CN119786564A_ABST
Patent Text Reader

Abstract

The invention provides a mixed solid electrolyte coated positive electrode material and a preparation method thereof, a positive plate, a solid-state battery and power-related equipment, and relates to the technical field of new energy. The mixed solid electrolyte-coated positive electrode material provided by the invention comprises a positive electrode material and a mixed solid electrolyte coating the surface of the positive electrode material, wherein the mixed solid electrolyte comprises an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte. According to the positive electrode material wrapped by the mixed solid-state electrolyte, the oxide solid-state electrolyte provides mechanical properties, the sulfide solid-state electrolyte provides ionic conductivity, the halide solid-state electrolyte provides a stable interface, and the combination of the three solid-state electrolytes can effectively improve the structural stability and conductivity of the positive electrode material; therefore, the cycling stability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new energy technology, and in particular to a positive electrode material wrapped in a hybrid solid electrolyte and a preparation method thereof, a positive electrode sheet, a solid-state battery and electrical equipment. Background Art

[0002] As the global demand for clean energy grows, lithium-ion batteries are widely used in various electronic devices and electric vehicles as an efficient and environmentally friendly energy storage method. However, traditional lithium-ion batteries mainly use liquid electrolytes, which have safety hazards such as flammability and explosion. Therefore, the development of safe and stable solid-state batteries has become an important research direction.

[0003] However, during the charge and discharge process of existing solid-state batteries, the interface between the positive electrode material and the solid electrolyte is poorly stable, which easily leads to battery capacity decay. Summary of the invention

[0004] The purpose of this application is to provide a positive electrode material wrapped in a hybrid solid electrolyte and its preparation method, a positive electrode sheet, a solid-state battery and electrical equipment, aiming to solve the problem that the interface between the existing positive electrode material and the solid electrolyte is poorly stable, which easily leads to capacity decay of the solid-state battery.

[0005] To achieve the above objectives, the present application provides a positive electrode material wrapped in a hybrid solid electrolyte, comprising: a positive electrode material and a hybrid solid electrolyte wrapped on the surface of the positive electrode material, wherein the hybrid solid electrolyte comprises an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte.

[0006] In some embodiments, the particle size of the sulfide solid electrolyte is larger than that of the halide solid electrolyte, and the particle size of the halide solid electrolyte is larger than that of the oxide solid electrolyte;

[0007] Optionally, the particle size of the sulfide solid electrolyte: the particle size of the halide solid electrolyte: the particle size of the oxide solid electrolyte = (100-500): (30-70): (2-7).

[0008] In some embodiments, at least one of the following conditions is met:

[0009] A. The particle size of the sulfide solid electrolyte is 1-5 μm;

[0010] B. The particle size of the halide solid electrolyte is 300-700nm;

[0011] C. The particle size of the oxide solid electrolyte is 20-70 nm.

[0012] In some embodiments, the mass of the sulfide solid electrolyte is greater than the sum of the mass of the oxide solid electrolyte and the mass of the halide solid electrolyte;

[0013] Optionally, the mass ratio of the oxide solid electrolyte, the sulfide solid electrolyte and the halide solid electrolyte is (0.1-1):10:(0.5-5).

[0014] In some embodiments, the oxide solid electrolyte comprises: Li 1+x Al x Ti 2-x (PO4)3、Li 7-x Ln3Z 2- x M x O 12 (M=Ta,Nb)(0≤x<2), Li x La 2 / 3-x TiO3, LiAlO2, Li2ZrO3 and Li4Ti5O 12 Any one or more of the following;

[0015] In some embodiments, the sulfide solid electrolyte includes: Li3PS4, 70Li2S·30P2S5, 80Li2S·20P2S5, 75Li2S·25P2S5, Li 10 GeP2S 12 and any one or more of Li6PS5X (X=Cl, Br or I);

[0016] In some embodiments, the molecular formula of the halide solid electrolyte is Li3AE6; wherein A is a positive trivalent metal, preferably, A is In, Sc or Y, and E is at least one of F, Cl and Br;

[0017] In some embodiments, the positive electrode material includes lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, binary material lithium nickel cobalt oxide, binary material lithium nickel manganese oxide, ternary material lithium nickel cobalt manganese oxide, ternary material lithium nickel cobalt aluminum oxide, lithium-rich manganese-based positive electrode material, and any one of the modified dopants of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, binary material lithium nickel cobalt oxide, binary material lithium nickel manganese oxide, ternary material lithium nickel cobalt manganese oxide, ternary material lithium nickel cobalt aluminum oxide and lithium-rich manganese-based positive electrode materials.

[0018] In some embodiments, at least one of the following conditions is met:

[0019] A. The mass ratio of the sum of the mass of the oxide solid electrolyte, the sulfide solid electrolyte and the halide solid electrolyte to the mass of the positive electrode material is 1:2 to 2:1;

[0020] B. The room temperature ionic conductivity of the mixed solid electrolyte is 10 -4 -10 -2 S / cm.

[0021] The present application also provides a method for preparing the above-mentioned mixed solid electrolyte-wrapped positive electrode material, comprising:

[0022] Mixing the oxide solid electrolyte, the sulfide solid electrolyte, and the halide solid electrolyte to obtain a mixed solid electrolyte;

[0023] The mixed solid electrolyte is wrapped on the surface of the positive electrode material by ball milling to obtain the positive electrode material wrapped by the mixed solid electrolyte.

[0024] The present application also provides a positive electrode sheet, comprising the positive electrode material wrapped by the above-mentioned mixed solid electrolyte.

[0025] The present application also provides a solid-state battery, comprising a positive electrode material wrapped in the above-mentioned mixed solid electrolyte, or comprising the above-mentioned positive electrode sheet.

[0026] The present application also provides an electrical device, including the above-mentioned solid-state battery.

[0027] Compared with the prior art, the beneficial effects of this application include:

[0028] The positive electrode material wrapped by the hybrid solid electrolyte provided in the present application includes a positive electrode material and a hybrid solid electrolyte wrapped on the surface of the positive electrode material, and the hybrid solid electrolyte includes an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte. The present application designs a positive electrode material wrapped by a hybrid solid electrolyte, wherein the oxide solid electrolyte provides mechanical properties, the sulfide solid electrolyte provides ionic conductivity, and the halide solid electrolyte provides a stable interface. The combination of the three solid electrolytes can effectively improve the structural stability and conductivity of the positive electrode material, thereby improving the cycle stability of the battery. Compared with the prior art, this method can more effectively solve the stability problem of the interface between the positive electrode material and the electrolyte, and reduce the capacity decay of the battery; the hybrid solid electrolyte of the present application has high conductivity, which can improve the charge and discharge efficiency of the battery. Compared with the prior art, this method can more effectively solve the problems of low conductivity and poor interface of the solid electrolyte, and improve the overall performance of the battery.

[0029] The sulfide solid-state full battery preparation process provided in this application is simple, low-cost, and is conducive to large-scale application. Compared with the prior art, this method can more effectively solve the problem of complex and high-cost preparation process of sulfide solid-state full batteries, which is conducive to its practical application. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0031] Figure 1 A schematic structural diagram of an embodiment of a positive electrode material wrapped with a hybrid solid electrolyte of the present application;

[0032] Figure 2 A schematic flow chart of a method for preparing a positive electrode material wrapped with a hybrid solid electrolyte of the present application;

[0033] Figure 3 This is a SEM image of the positive electrode material wrapped with the hybrid solid electrolyte of Example 1. DETAILED DESCRIPTION

[0034] As used herein:

[0035] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0036] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0037] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0038] In these examples, parts and percentages are by mass unless otherwise indicated.

[0039] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0040] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0041] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0042] The present application provides a positive electrode material wrapped with a hybrid solid electrolyte, comprising: a positive electrode material and a hybrid solid electrolyte wrapped on the surface of the positive electrode material, wherein the hybrid solid electrolyte comprises an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte.

[0043] The present application designs a positive electrode material wrapped in a hybrid solid electrolyte. The oxide solid electrolyte provides mechanical properties, the sulfide solid electrolyte provides ionic conductivity, and the halide solid electrolyte provides a stable interface. The combination of the three solid electrolytes can effectively improve the structural stability and conductivity of the positive electrode material, thereby improving the cycle stability of the battery. Compared with the prior art, this method can more effectively solve the stability problem of the interface between the positive electrode material and the electrolyte, and reduce the capacity decay of the battery. The hybrid solid electrolyte of the present application has high conductivity and can improve the charge and discharge efficiency of the battery. Compared with the prior art, this method can more effectively solve the problems of low conductivity and poor interface of the solid electrolyte, and improve the overall performance of the battery.

[0044] In some embodiments, the particle size of the sulfide solid electrolyte is larger than that of the halide solid electrolyte, and the particle size of the halide solid electrolyte is larger than that of the oxide solid electrolyte.

[0045] See also Figure 1 , Figure 1This is a schematic structural diagram of an embodiment of a positive electrode material wrapped with a hybrid solid electrolyte of the present application, Figure 1 The positive electrode material is exemplified by the ternary material nickel cobalt manganese oxide (NCM particles), the sulfide solid electrolyte (sulfide) is large particles, the halide solid electrolyte (halide) is medium particles, and the oxide solid electrolyte (oxide) is small particles.

[0046] The role of large particles of sulfide solid electrolyte is to provide fast ion transmission channels to ensure the overall conductivity of the positive electrode. Its larger particles can reduce the total interface area, reduce interface resistance and the possibility of side reactions. The role of particles in halide solid electrolytes is to act as an intermediate layer, which can buffer the chemical mismatch between sulfide solid electrolytes and NCM positive electrodes, reduce interface side reactions, and provide additional ion transmission channels to maintain interface conductivity. The role of small particles of oxide solid electrolytes is to form a protective layer to prevent direct contact between the NCM positive electrode and the sulfide solid electrolyte, which can trigger interfacial decomposition reactions. Small particles have a large specific surface area and can be evenly distributed on the surface of the positive electrode, enhancing the quality of interface contact. Improve the mechanical stability of the positive electrode and avoid particle peeling or cracking caused by volume changes during the cycle.

[0047] The synergistic effect of large sulfide solid electrolyte particles, medium halide solid electrolyte particles and small oxide solid electrolyte particles can optimize ion conduction. The large sulfide solid electrolyte particles provide the dominant ion transport channel, the medium halide solid electrolyte particles supplement the interfacial conductivity, and the small oxide solid electrolyte particles enhance the interfacial stability. It can also improve the interface stability. The halide solid electrolyte and the oxide solid electrolyte protect the interface between the sulfide solid electrolyte and the positive electrode chemically and mechanically, respectively, reducing interfacial decomposition and impedance growth. It can also extend the cycle life. Through the synergistic effect of the three materials, the ion conduction is improved, the interfacial reaction is slowed down, and the capacity retention rate of the battery is improved.

[0048] Optionally, the particle size of the sulfide solid electrolyte: the particle size of the halide solid electrolyte: the particle size of the oxide solid electrolyte = (100-500): (30-70): (2-7).

[0049] In some embodiments, the particle size of the sulfide solid electrolyte is 1-5 μm, for example, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm or any value between 1-5 μm.

[0050] In some embodiments, the particle size of the halide solid electrolyte is 300-700 nm, for example, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm or any value between 300-700 nm.

[0051] In some embodiments, the particle size of the oxide solid electrolyte is 20-70 nm, for example, it can be 20 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm or any value between 20-70 nm.

[0052] In some embodiments, the mass of the sulfide solid electrolyte is greater than the sum of the mass of the oxide solid electrolyte and the mass of the halide solid electrolyte. Sulfide solid electrolytes have high conductivity and good flexibility, and require a large amount to fill the gaps between particles and optimize the ion conduction network; halide solid electrolytes have moderate conductivity and flexibility, and a relatively small amount can balance interface stability and conduction performance; oxide solid electrolytes have low conductivity but strong chemical stability, and a small amount can meet the interface protection requirements, thereby maximizing the battery energy density.

[0053] In some embodiments, the mass ratio of the oxide solid electrolyte, the sulfide solid electrolyte and the halide solid electrolyte is (0.1-1):10:(0.5-5), for example, it can be 0.1:10:0.5, 0.2:10:1, 0.5:10:1, 0.6:10:2, 1:10:5, 1:10:1 or any ratio between (0.1-1):10:(0.5-5).

[0054] In some embodiments, the oxide solid electrolyte comprises: Li 1+x Al x Ti 2-x (PO4)3、Li 7-x Ln3Z 2- x M x O 12 (M=Ta,Nb)(0≤x<2), Li x La 2 / 3-x TiO3, LiAlO2, Li2ZrO3 and Li4Ti5O 12 Any one or more of .

[0055] In some embodiments, the sulfide solid electrolyte includes: Li3PS4, 70Li2S·30P2S5, 80Li2S·20P2S5, 75Li2S·25P2S5, Li 10 GeP2S12 (LGPS) and Li6PS5X (X = Cl, Br or I) any one or more.

[0056] In some embodiments, the molecular formula of the halide solid electrolyte is Li3AE6; wherein A is a trivalent metal, preferably, A is In, Sc or Y, and E is at least one of F, Cl, and Br.

[0057] In some embodiments, the positive electrode material includes lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, binary material lithium nickel cobalt oxide, binary material lithium nickel manganese oxide, ternary material lithium nickel cobalt manganese oxide, ternary material lithium nickel cobalt aluminum oxide, lithium-rich manganese-based positive electrode material, and any one of the modified dopants of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, binary material lithium nickel cobalt oxide, binary material lithium nickel manganese oxide, ternary material lithium nickel cobalt manganese oxide, ternary material lithium nickel cobalt aluminum oxide and lithium-rich manganese-based positive electrode materials.

[0058] In some embodiments, the mass ratio of the sum of the masses of the oxide solid electrolyte, the sulfide solid electrolyte and the halide solid electrolyte to the positive electrode material is 1:2 to 2:1, for example, it can be 1:2, 1:1, 3:2, 2:1 or any ratio between 1:2 and 2:1.

[0059] In some embodiments, the room temperature ionic conductivity of the hybrid solid electrolyte is 10 -4 -10 -2 S / cm.

[0060] The present application also provides a method for preparing the above-mentioned mixed solid electrolyte-wrapped positive electrode material, please refer to Figure 2 ,include:

[0061] S100: mixing an oxide solid electrolyte, a sulfide solid electrolyte, and a halide solid electrolyte to obtain a mixed solid electrolyte;

[0062] S200: coating the mixed solid electrolyte on the surface of the positive electrode material by ball milling to obtain the positive electrode material coated with the mixed solid electrolyte.

[0063] The present application also provides a positive electrode sheet, comprising the positive electrode material wrapped by the above-mentioned mixed solid electrolyte.

[0064] The present application also provides a solid-state battery, comprising a positive electrode material wrapped in the above-mentioned mixed solid electrolyte, or comprising the above-mentioned positive electrode sheet.

[0065] The sulfide solid-state full battery preparation process provided in this application is simple, low-cost, and is conducive to large-scale application. Compared with the prior art, this method can more effectively solve the problem of complex and high-cost preparation process of sulfide solid-state full batteries, which is conducive to its practical application.

[0066] The present application also provides an electrical device, including the above-mentioned solid-state battery.

[0067] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0068] Example 1

[0069] This embodiment provides a positive electrode material wrapped with a mixed solid electrolyte, and the preparation method thereof comprises the following steps:

[0070] Step 1: Select an oxide solid electrolyte Li7La3Zr2O with high conductivity 12 (LLZO) with a particle size of 50nm, sulfide solid electrolyte Li6PS5Cl with a particle size of 3μm, and halide solid electrolyte Li3InCl6 with a particle size of 500nm. 10mg LLZO, 200mg LiPSCl and 20mg Li3InCl6 were mixed to obtain a mixed solid electrolyte. The conductivity of the mixed solid electrolyte is 1.5*10 -3 S / cm, and can exist stably at room temperature.

[0071] Step 2: Prepare the positive electrode material wrapped by the mixed solid electrolyte by ball milling. First, take the ternary material nickel cobalt manganese oxide as the positive electrode material, mix the ternary material nickel cobalt manganese oxide and the mixed solid electrolyte of step 1 in a mass ratio of 1:1, and ball mill at 100 rpm / min for 2 hours to obtain the positive electrode material wrapped by the mixed solid electrolyte of Example 1, and its SEM image is as follows: Figure 3 shown.

[0072] This embodiment also provides a sulfide solid-state full battery, and its preparation method includes the following steps:

[0073] The positive electrode material wrapped by the mixed solid electrolyte of Example 1 is assembled with the sulfide solid electrolyte (Li6PS5Cl) and the negative electrode material (Li metal) into a sulfide solid-state full battery. The specific operation is to mix the positive electrode material, the sulfide solid electrolyte and the negative electrode material in a mass ratio of 1:1:1, and press them at 500°C and 500MPa for 2 hours under argon protection by hot pressing to obtain the sulfide solid-state full battery of Example 1.

[0074] The prepared sulfide solid-state full battery was tested for performance. The test conditions were: charge and discharge tests were performed at room temperature with a current density of 0.1C and a voltage range of 2.5-4.2V.

[0075] Example 2

[0076] This embodiment provides a positive electrode material wrapped with a mixed solid electrolyte. The difference between the preparation method thereof and that of Embodiment 1 is that the oxide solid electrolyte of Embodiment 2 is replaced by LATP, and the remaining steps are the same as those of Embodiment 1.

[0077] Example 3

[0078] This embodiment provides a positive electrode material wrapped with a hybrid solid electrolyte. The difference between its preparation method and that of Embodiment 1 is that Li3InCl6 is replaced by Li3ScCl6, and the remaining steps are the same as those of Embodiment 1.

[0079] Example 4

[0080] This embodiment provides a positive electrode material wrapped with a mixed solid electrolyte. The difference between its preparation method and that of Example 1 is that the mass of the sulfide solid electrolyte in Example 4 is 100 mg, and the remaining steps are the same as those in Example 1.

[0081] Example 5

[0082] This embodiment provides a positive electrode material wrapped with a mixed solid electrolyte. The difference between its preparation method and that of embodiment 1 is that the mass of the halide solid electrolyte in embodiment 5 is 10 mg, and the remaining steps are the same as those in embodiment 1.

[0083] Example 6

[0084] This embodiment provides a positive electrode material wrapped in a mixed solid electrolyte. The difference between its preparation method and that of Example 1 is that the particle size of the oxide solid electrolyte is 30 nm, the particle size of the sulfide solid electrolyte is 1 μm, and the particle size of the halide solid electrolyte is 300 nm. The remaining steps are the same as those of Example 1.

[0085] Example 7

[0086] This embodiment provides a positive electrode material wrapped in a mixed solid electrolyte. The difference between its preparation method and that of Example 1 is that the particle size of the oxide solid electrolyte is 70 nm, the particle size of the sulfide solid electrolyte is 5 μm, and the particle size of the halide solid electrolyte is 700 nm. The remaining steps are the same as those of Example 1.

[0087] Comparative Example 1

[0088] This comparative example provides a positive electrode material wrapped with a solid electrolyte. The difference between the preparation method thereof and that of Example 1 is that the solid electrolyte of Comparative Example 1 only includes an oxide solid electrolyte, and the remaining steps are the same as those of Example 1.

[0089] Comparative Example 2

[0090] This comparative example provides a positive electrode material wrapped with a solid electrolyte. The difference between the preparation method thereof and that of Example 1 is that the solid electrolyte of Comparative Example 2 only contains a sulfide solid electrolyte, and the remaining steps are the same as those of Example 1.

[0091] Comparative Example 3

[0092] This comparative example provides a positive electrode material wrapped with a solid electrolyte. The difference between the preparation method thereof and that of Example 1 is that the solid electrolyte of Comparative Example 3 only contains a halide solid electrolyte, and the remaining steps are the same as those of Example 1.

[0093] Comparative Example 4

[0094] This comparative example provides a positive electrode material wrapped with a mixed solid electrolyte. The difference between its preparation method and that of Example 1 is that the solid electrolyte of Comparative Example 4 only contains an oxide solid electrolyte and a halide solid electrolyte, and the remaining steps are the same as those of Example 1.

[0095] Comparative Example 5

[0096] This comparative example provides a positive electrode material wrapped with a mixed solid electrolyte. The difference between its preparation method and that of Example 1 is that the solid electrolyte of Comparative Example 5 only contains a halide solid electrolyte and a sulfide solid electrolyte, and the remaining steps are the same as those of Example 1.

[0097] Comparative Example 6

[0098] This comparative example provides a positive electrode material wrapped with a mixed solid electrolyte. The difference between its preparation method and that of Example 1 is that the solid electrolyte of Comparative Example 6 only contains an oxide solid electrolyte and a sulfide solid electrolyte, and the remaining steps are the same as those of Example 1.

[0099] Comparative Example 7

[0100] This comparative example provides a positive electrode material wrapped with a mixed solid electrolyte. The difference between its preparation method and that of Example 1 is that the particle size of the oxide solid electrolyte is 80 nm, and the remaining steps are the same as those of Example 1.

[0101] Comparative Example 8

[0102] This comparative example provides a positive electrode material wrapped with a mixed solid electrolyte. The difference between its preparation method and that of Example 1 is that the particle size of the oxide solid electrolyte is 10 nm, and the remaining steps are the same as those of Example 1.

[0103] Comparative Example 9

[0104] This comparative example provides a positive electrode material wrapped with a mixed solid electrolyte. The difference between its preparation method and that of Example 1 is that the particle size of the sulfide solid electrolyte is 6 μm, and the remaining steps are the same as those of Example 1.

[0105] Comparative Example 10

[0106] This comparative example provides a positive electrode material wrapped with a mixed solid electrolyte. The difference between the preparation method thereof and that of Example 1 is that the particle size of the sulfide solid electrolyte is 0.9 μm, and the remaining steps are the same as those of Example 1.

[0107] Comparative Example 11

[0108] This comparative example provides a positive electrode material wrapped with a mixed solid electrolyte. The difference between its preparation method and that of Example 1 is that the particle size of the halide solid electrolyte is 800 nm, and the remaining steps are the same as those of Example 1.

[0109] Comparative Example 12

[0110] This comparative example provides a positive electrode material wrapped with a mixed solid electrolyte. The difference between its preparation method and that of Example 1 is that the particle size of the halide solid electrolyte is 200 nm, and the remaining steps are the same as those of Example 1.

[0111] Comparative Example 13

[0112] This comparative example provides a positive electrode material wrapped with a mixed solid electrolyte. The difference between its preparation method and that of Example 1 is that the halide solid electrolyte in Comparative Example 13 is replaced by Li3ZrCl7, and the remaining steps are the same as those in Example 1.

[0113] The battery impedance test method is as follows:

[0114] 1. Grind the mixed solid electrolyte and weigh 100-200 mg into a solid-state battery test mold (Zhongke Wanyuan, model: JYGS1-10, inner diameter 10 mm), with stainless steel at both ends as blocking electrodes, press at 3-6T and hold for 1-10 minutes, maintain the pressure at 2.5-3.5T, use Bio-Logic equipment, set the frequency to 1MHz~1Hz, and measure the data;

[0115] 2. Fit the data according to an equivalent circuit model (such as a series resistance and capacitance model) to calculate the resistance value (R) of the electrolyte, which is usually the x-axis intercept in the high-frequency region;

[0116] 3. Take out the solid electrolyte and use a screw micrometer to measure the thickness l and radius r of the solid electrolyte ceramic sheet. According to δ=l / Rπr 2 Calculate the room temperature ionic conductivity.

[0117] Note: 1. Sample environment: Keep the test environment dry to avoid performance degradation of hygroscopic electrolytes (such as sulfides). 2. Signal stability: Multiple measurements ensure data consistency.

[0118] The electrochemical performance of the sulfide solid-state full battery of each embodiment and comparative example is shown in Table 1.

[0119] Table 1 Electrochemical performance of sulfide solid-state full batteries of various embodiments and comparative examples

[0120]

[0121]

[0122] According to Table 1, in Example 1 to Example 7 and Comparative Example 7 to Comparative Example 12, three solid electrolytes are mixed to coat the surface of the positive electrode material, compared with Comparative Example 1 to Comparative Example 6, which only use one or two solid electrolytes to coat the surface of the positive electrode material, the battery impedance is greatly reduced after 100 cycles, that is, the conductivity of the positive electrode material is high, and the three solid electrolytes in Example 1 to Example 7 can improve the structural stability of the positive electrode material under the appropriate dosage ratio and particle size ratio, so that the 100-cycle capacity retention rate is higher than that of Comparative Example 7 to Comparative Example 12. According to Comparative Example 13, the halide solid electrolyte Li3ZrCl7 used in Comparative Example 13 does not help much to the stability of the positive electrode material, because the ionic conductivity of Li3ZrCl7 is low and the electrochemical stability is poor.

[0123] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0124] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A positive electrode material wrapped with a mixed solid electrolyte, characterized in that: include: A positive electrode material and a mixed solid electrolyte wrapped on the surface of the positive electrode material, wherein the mixed solid electrolyte includes an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte.

2. The positive electrode material wrapped with a hybrid solid electrolyte according to claim 1, characterized in that: The particle size of the sulfide solid electrolyte is larger than that of the halide solid electrolyte, and the particle size of the halide solid electrolyte is larger than that of the oxide solid electrolyte; Optionally, the particle size of the sulfide solid electrolyte: the particle size of the halide solid electrolyte: the particle size of the oxide solid electrolyte = (100-500): (30-70): (2-7).

3. The positive electrode material wrapped with a hybrid solid electrolyte according to claim 2, characterized in that: At least one of the following conditions is met: A. The particle size of the sulfide solid electrolyte is 1-5 μm; B. The particle size of the halide solid electrolyte is 300-700nm; C. The particle size of the oxide solid electrolyte is 20-70 nm.

4. The positive electrode material wrapped with a hybrid solid electrolyte according to claim 1, characterized in that: The mass of the sulfide solid electrolyte is greater than the sum of the mass of the oxide solid electrolyte and the mass of the halide solid electrolyte; Optionally, the mass ratio of the oxide solid electrolyte, the sulfide solid electrolyte and the halide solid electrolyte is (0.1-1): 10:(0.5~5)。 5. The positive electrode material wrapped with a hybrid solid electrolyte according to claim 1, characterized in that: At least one of the following conditions is met: A. The oxide solid electrolyte includes: Li 1+x Al x Ti 2-x (PO4)3、Li 7-x LqCy 2-x M x O 12 (M=Ta,Nb)(0≤x<2), Li x La 2 / 3-x TiO3, LiAlO2, Li2ZrO3 and Li4Ti5O 12 Any one or more of the following; B. The sulfide solid electrolyte includes: Li3PS4, 70Li2S·30P2S5, 80Li2S·20P2S5, 75Li2S·25P2S5, Li 10 GeP2S 12 and any one or more of Li6PS5X (X=Cl, Br or I); C. The molecular formula of the halide solid electrolyte is Li3AE6; wherein A is a positive trivalent metal, preferably, A is In, Sc or Y, and E is at least one of F, Cl and Br; D. The positive electrode material includes lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, binary material lithium nickel cobalt oxide, binary material lithium nickel manganese oxide, ternary material lithium nickel cobalt manganese oxide, ternary material lithium nickel cobalt aluminum oxide, lithium-rich manganese-based positive electrode material and any one of the modified dopants of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, binary material lithium nickel cobalt oxide, binary material lithium nickel manganese oxide, ternary material lithium nickel cobalt manganese oxide, ternary material lithium nickel cobalt aluminum oxide and lithium-rich manganese-based positive electrode material.

6. The positive electrode material wrapped with a hybrid solid electrolyte according to any one of claims 1 to 5, characterized in that: At least one of the following conditions is met: A. The mass ratio of the sum of the mass of the oxide solid electrolyte, the sulfide solid electrolyte and the halide solid electrolyte to the mass of the positive electrode material is 1:2 to 2:1; B. The room temperature ionic conductivity of the mixed solid electrolyte is 10 -4 -10 -2 S / cm.

7. A method for preparing a positive electrode material wrapped with a hybrid solid electrolyte according to any one of claims 1 to 6, characterized in that: include: Mixing the oxide solid electrolyte, the sulfide solid electrolyte, and the halide solid electrolyte to obtain a mixed solid electrolyte; The mixed solid electrolyte is wrapped on the surface of the positive electrode material by ball milling to obtain the positive electrode material wrapped by the mixed solid electrolyte.

8. A positive electrode sheet, characterized in that: A positive electrode material wrapped with a hybrid solid electrolyte according to any one of claims 1 to 6.

9. A solid-state battery, characterized in that: A positive electrode material wrapped with a hybrid solid electrolyte according to any one of claims 1 to 6, or a positive electrode sheet according to claim 8.

10. An electrical equipment, characterized in that: Including the solid-state battery as described in claim 9.

Citation Information

Patent Citations

  • Composite positive electrode, solid-state lithium ion secondary battery, and electric device

    CN115172653A

  • Solid electrolyte composite material and lithium battery

    CN116365017A

  • All-solid-state secondary battery and preparation method thereof

    CN117039133A

  • Solid electrolyte membrane and preparation method and application thereof

    CN117059885A

  • Solid-state positive electrode, preparation method thereof and solid-state battery

    CN117558870A

Cited By

  • Positive plate and preparation method thereof, all-solid-state battery, battery assembly and electric equipment

    CN120261477A

  • Positive electrode sheet and preparation method thereof, all-solid-state battery, battery assembly, and electrical equipment

    CN120261477B

  • Preparation method and application of composite positive electrode containing halide electrolyte

    CN120999099A